Hubungan Antara Berat Badan Lahir dan Kejadian Underweight di Kelurahan Bugel, Karawaci - Pundra Dara Avindharin; Agnia Nurul Hikmah; Citra Sari Nasrianti (JUMAGI (Jurnal Madani Gizi Indonesia), 2024)
Background: Underweight is a condition in which a child's weight is lower than what is expected for their age. The condition of underweight in children can lead to disruptions in physical, mental, behavioral, and cognitive health. One of the factors contributing to the onset of underweight is the anthropometric characteristics at birth, such as birth weight and birth length. The aim of this study is to determine the relationship between birth weight and its association with underweight incidence in the Bugel Subdistrict, Karawaci, Tangerang. Subjects and methods: This study is a cross-sectional type. The subjects of this study consist of children aged 0 to 60 months living in the Bugel Subdistrict, Tangerang City. The sample was selected using purposive sampling method with a total of 100 respondents. Primary data were collected through the use of questionnaires in direct interviews with the respondents. Data analysis was performed univariately by distributing frequencies, while bivariate analysis was conducted using the Chi-Square test. Results: From this study, it was found that Birth Weight has a significant relationship with underweight incidence (p value = 0.034). Conclusion: Children with Birth Weight <2500 grams are 7.545 times more at risk of experiencing underweight incidence compared to Birth Weight >=2500 grams. Keywords: Underweight, Child Gender, Child Age, Low Birth Weight (BBLR).